POLITENESS STRATEGIES ON SOCIAL MEDIA AND THEIR IMPACT ON THE MENTAL HEALTH OF STUDENTS AT HASANUDDIN UNIVERSITY - Aj, Andi Meirling; Wahyuddin, Wahyuddin; Lukman, Lukman; Rismayanti, Rismayanti; Kaharuddin, Mutahharah Nemin; Indarwati, Indarwati; Musfira, Musfira; Hardiman, Hardiman (Universitas Negeri Makassar, 2025)
This study investigates the use of politeness strategies in digital interactions and their impact on students' mental health and learning motivation. Employing a mixed-method approach with pragmatic analysis, data were collected from 204 student respondents through an online questionnaire. The data source in this study is Hasanuddin University students who use social media. The sample was determined using purposive sampling. The inclusion criteria are active Hasanuddin University students from various study programs, aged between 18 and 24 years, who use social media, are willing to voluntarily complete the questionnaire, and have a basic understanding of the context of communication on social media. Data was collected through an online questionnaire. The findings show that positive and negative politeness strategies promote emotional comfort and motivation, while bald on record, off record, and withhold tend to cause confusion, emotional stress, and decreased motivation. The study emphasizes the importance of polite digital communication in supporting students' well-being and academic engagement.